Funkcje jakości popytu na mięso w Polsce - Kędelski, Mieczysław (Wydział Prawa i Administracji UAM, 1972)
A logical supplement of the quantity function of demand and of the expenditure function is the so called "quality" function of demand. If it can be assumed that internal quality relations of groups of consumers' goods are reflected in price relations of those articles, the differentiation of the mean weighted group price may be accepted as a measure reflecting quality changes in the group. The quality function may be then presented by the group price function. This paper is devoted to economic identification of the indicated relations and statistical verification of the presented hypothesis. The hypothesis runs as follows: the quality demand for a given aggregate of meat is increasing with the growth of the consumers' affluence. The author based the empirical analysis on the results of family budget studies in Poland in the years 1967 - 1970.
Quality Functions of Demand for Meat in Poland